Striking antitumor activity of a methinium system with incorporated quinoxaline unit obtained by spontaneous cyclization - Bříza, T; Králová, J; Dolenský, B; Rimpelová, S; Kejík, Z; Ruml, T; Hajdúch, M; Džubák, P; Mikula, I; Martásek, P; Poučková, P; Král, V (Chembiochem, 2015)
A novel pentamethinium salt was synthesized with an unforeseen expanded conjugated quinoxaline unit directly incorporated into a pentamethinium chain. The compound exhibited high fluorescence intensity, selective mitochondrial localization, high cytotoxicity, and selectivity toward malignant cell lines, and resulted in remarkable in vivo suppression of tumor growth in mice.
Keywords: methinium salt; protinádorové látky; Neoplasms; Cell Line, Tumor; cancer; tumor growth suppression; Cyclization; chinoxaliny; hexamethonium; quinoxaline; mitochondrial localization; fluorescent probes; Animals; zvířata; Hexamethonium; myši; cyklizace; nádory; Quinoxalines; nádorové buněčné linie; Mice; Antineoplastic Agents